Evaluation of the main processing parameters influencing the performance of poly(vinylidene fluoride – trifluorethylene) lithium ion battery separators - Costa, C. M. (2013)
Poly(vinylidene fluoride – trifluorethylene) membranes are evaluated for lithium ion battery separator applications. Some of the main parameters affecting separator performance such as porosity, dehydration of lithium ions and processing technique (Li-ion uptake versus composite formation) are investigated. The polymer characteristics, as determined by infrared spectroscopy, do not change as a function of porosity, dehydration of lithium ions in the electrolyte solution or processing technique. The electrochemical impedance spectroscopy represented through the Nyquist plot, Bode plot and the ionic conductivity as a function of temperature, strongly depends on the aforementioned paramenters. The membrane that exhibits the highest ionic conductivity is a porous membrane without dehydration of lithium ions and prepared by the uptake technique. The performance of the membrane for battery applications are therefore strongly influenced both by porosity and processing technique.